Barriers to Learning, Achievement, Institutional Identities and Professionalization - Aparicio, Miriam Teresita (2016)
This study is part of the broader research program on University Quality Assessment. The aim was to go deep into the causesfor delay in finishing studies in Argentina. This brings about a problem at the institutional and personal levels (disappointment,depression, frustration,?). In 1995 the Department of University Polices called for a contest to analyze the Causes forDropout, and we won it. It had been preceded by another project (still in progress) dealing with graduates from differentfaculties. The combination of different factors (basic, personal, occupational, structural, institutional and psychosocial ones),concerning the 20 years of the UNCuyo and 6 Faculties/Study Courses (1987-2004; N 299 individuals) gradually showedwhich factors predicted different achievement levels, as well as the strongest underlying reasons of the individuals? coursesof action. The quantitative-qualitative method was applied. In this paper, we focus on a motivational factor: Fear of Failure;one of the predictive ones for delay along with others, as it showed differentiated profiles according to Academic Units andCourses of Studies (Disciplinary and institutional identities). The results are very relevant within a context in which delay instudies is quite evident. The intervention and support systems and Professionalization to improve University Quality and thestudents? personal and professional achievement are necessary. Then, Performance, Identities and Professionalizationcomprise macroanalysis (national policies), mesoanalysis (questions differentiated as Academic Units), and microanalysis(individuals who are affected in their personal health and self-fulfillment due to the lack of non-disciplinary programs).